2013
DOI: 10.1371/journal.pone.0059756
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of Early Senescence in Multiple Myeloma Bone Marrow Mesenchymal Stromal Cells

Abstract: BackgroundIn multiple myeloma, bone marrow mesenchymal stromal cells support myeloma cell growth. Previous studies have suggested that direct and indirect interactions between malignant cells and bone marrow mesenchymal stromal cells result in constitutive abnormalities in the bone marrow mesenchymal stromal cells.Design and MethodsThe aims of this study were to investigate the constitutive abnormalities in myeloma bone marrow mesenchymal stromal cells and to evaluate the impact of new treatments.ResultsWe dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
101
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 66 publications
(69 reference statements)
16
101
1
Order By: Relevance
“…Nevertheless, the expression status of CRISP3 and its potential as a peripheral blood biomarker in human MM remains to be determined. Data of human peripheral blood samples from the GEO repository may be merged together to produce a large sample data, and this super array data possesses a distinguished expression pattern, as observed in previous studies that used tissue samples (31,32). The present study identified that the gene expression of MM peripheral blood also possessed a marked pattern, even in the merged data.…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, the expression status of CRISP3 and its potential as a peripheral blood biomarker in human MM remains to be determined. Data of human peripheral blood samples from the GEO repository may be merged together to produce a large sample data, and this super array data possesses a distinguished expression pattern, as observed in previous studies that used tissue samples (31,32). The present study identified that the gene expression of MM peripheral blood also possessed a marked pattern, even in the merged data.…”
Section: Discussionsupporting
confidence: 64%
“…However, while UC-, AD-, and nBM-MSCs preserved their morphology during their culture passages, BM-MSCs from MM patients failed to maintain their shape till the third passage and underwent early senescence, as shown by their larger, flattened morphology and intense cytoplasmic granularity. This aspect of BM-MSCs has recently been correlated to the pathophysiology of MM, since senescent MM-conditioned MSCs are more likely to secrete factors, such as IL-6, IGF-1, and OPG, promoting oncogenic modifications of the MM microenvironment [31]. We observed that myelomatous BM-MSCs clearly reinforce the clonogenicity of most MM cell strains and hypothesized that this effect was due to an increased release of growth factors such as effect of the original influence of MM cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the BM microenvironment niche has received considerable attention in MDS pathophysiology since components of the cell niche, mainly MSCs, are defective in supporting normal hematopoiesis in MDS [14], mostly in myelopoiesis [15], and can induce dysplasia in hematopoietic precursors in vitro [16]. MSCs facilitate the self-renewal, survival, differentiation, and proliferation of hematopoietic cells through direct (cell-cell) and indirect (cytokine secretion) contact [17,18]. MSCs constitutively secrete a large number of cytokines and alterations in their levels can also serve as a safe haven for malignant hematopoietic cells, resulting in an important modification in MDS clones and offering protection against chemotherapeutic agents [19].…”
Section: Discussionmentioning
confidence: 99%